Remote Health Screening for the Elderly at the Posyandu during the Covid-19 Pandemic - Bryany Titi Santi; Nurlina Supartini; Thika Marliana; Nur Fitriah (MITRA: Jurnal Pemberdayaan Masyarakat, 2023)
Anxiety, cognitive impairment function, hypertension, obesity, cardiovascular disease, and stroke in elderly is increasing in Covid-19 pandemic. This can lower their quality of life. Meanwhile, Integrated elderly health service (posyandu) have been temporary suspended to prevent infection on elderly who are high risk for severe illness Covid-19. The aim of this activity is to facilitate elderly to access health service and connected the role of some institutions for providing appropriate intervention. The method of this activity was a discussion with related institutions in online health screening of elderly integrated health service. Then, we conduct health screening using online questionnaire. Based on data, we analyze elderly with health problems to get home visit for further examination and give therapy and education. Result of these activity, we found 58 persons (16,02%) with health problem, 42 (11,6%) persons are having mental emotional disorder, 205 (69,05%) with risk of fall, and 53 (14,6%) are having cognitive impairment, 37 and 133 are low nutrition and obesity. Only health institutions give intervention for those elderly with health problem and have to gain awareness and advocation for planning action for elderly based on their roles.